2020
DOI: 10.1016/j.isci.2020.101441
|View full text |Cite
|
Sign up to set email alerts
|

Residue-Specific Message Encoding in CD40-Ligand

Abstract: Summary CD40-Ligand (CD40L)-CD40 interaction regulates immune responses against pathogens, autoantigens, and tumor and transplantation antigens. Single amino acid mutations within the 115–155 amino acids stretch, which is responsible for CD40L functions, result in XIgM syndrome. We hypothesize that each of these amino acids of CD40L encodes specific message that, when decoded by CD40 signaling, induces a specific profile of functions. We observed that every single substitution in the XIgM-related am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Tbet, Gata3, Rorγt, and Foxp3 expression levels as well as the expression of CD4 + T cell surface markers such as CD69, CD39, CD132, CD122, CD28, CXCR5, CCR1, CCR6 were not significantly different. CD40L is a co-stimulatory receptor on Tfh cells [ 26 ] and also helps in immunoglobulin class switching, but there is no significant difference between GCB, Tfh cells, and concentrations of IgM and other immunoglobulins, indicating that expression of CD40L is similar in young WT and AMPK-KO mice. We have previously showed similar expression of Treg surface markers, except PD-1, Nrp1, and ICOS [ 14 ], suggesting that the newly generated young WT and AMPK-KO mice are almost phenotypically similar and have similar Th1, Th2, Th17, and Treg transcriptional profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Tbet, Gata3, Rorγt, and Foxp3 expression levels as well as the expression of CD4 + T cell surface markers such as CD69, CD39, CD132, CD122, CD28, CXCR5, CCR1, CCR6 were not significantly different. CD40L is a co-stimulatory receptor on Tfh cells [ 26 ] and also helps in immunoglobulin class switching, but there is no significant difference between GCB, Tfh cells, and concentrations of IgM and other immunoglobulins, indicating that expression of CD40L is similar in young WT and AMPK-KO mice. We have previously showed similar expression of Treg surface markers, except PD-1, Nrp1, and ICOS [ 14 ], suggesting that the newly generated young WT and AMPK-KO mice are almost phenotypically similar and have similar Th1, Th2, Th17, and Treg transcriptional profiles.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how alcohol activates p38γ MAPK. It has been proposed that the interaction of several upstream signaling molecules, such as CD40L and CD40, may result in p38 MAPK activation which stimulates diverse cytokine profile, transcription factors and oxidative stress ( 46 ). These processes may be involved metastasis or cancer stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ERK1/2 by PMA was subsequently demonstrated to be a prerequisite in committing K562 and other such cell lines to undergo megakaryocytic differentiation (Conde et al, 2010, Whalen et al, 1997). In addition, ERK activation by sCD40L was also shown to activate ERK leading to inhibition of cell proliferation and induction of apoptosis in K562 cells (Ren et al, 2016; Sarode et al, 2020). In agreement with these, we also observed that ORM indeed activated ERK1/2 and growth suppressor proteins p21 and p27 leading to growth arrest so that cells can exit the cell cycle and undergo differentiation.…”
Section: Discussionmentioning
confidence: 99%